Kompos dan Kapur Pertanian dalam Lubang Resapan Biopori Memperbaiki KTK Tanah dan Produktivitas Kopi Robusta Di Hutan Pendidikan UB Forest: Compost and Agriculture Lime in Biopore Infiltration Holes Improving Soil CEC and Coffee Productivity at the UB Forest location - Bintang Arfani, Deva Fatira; Lutfi, M Wasilul; Lestari, Nina Dwi; Ifadah, Nisfi Faridatul; Soemarno, Soemarno; Alivianisha Putri, Rr. Audry (Fakultas Pertanian Universitas Brawijaya, 2025)
PCoffee productivity in UB Forest has been categorized as low in recent years, ranging from approximately 100–400 kg ha⁻¹ year⁻¹. This low productivity is presumed to be associated with land suitability constraints, particularly soil chemical characteristics such as pH and cation exchange capacity (CEC). One approach to improving subsoil chemical properties is the application of compost and lime through biopore infiltration holes (LRB). This study aimed to analyze the effects of biopore infiltration holes filled with compost and lime on soil pH and CEC, as well as their relationship with coffee productivity. The experiment was arranged in a randomized block design with seven treatments and four replications, consisting of: P0 (control), P1 (empty biopore), P2 (biopore + 1.5 t ha⁻¹ lime), P3 (biopore + 10 t ha⁻¹ compost), P4 (biopore + 20 t ha⁻¹ compost), P5 (biopore + 10 t ha⁻¹ compost + 1.5 t ha⁻¹ lime), and P6 (biopore + 20 t ha⁻¹ compost + 1.5 t ha⁻¹ lime). The results showed that five months after application, treatment P2 significantly increased soil pH at depths of 0–30 cm and 30–60 cm. Treatment P6 increased soil CEC by 28.12% at 0–30 cm and by 21.78% at 30–60 cm. Regression analysis indicated that coffee productivity was influenced by soil CEC and base saturation (Kdd) at the 30–60 cm depth (Y = –4084.997 + 89.6751X₁ + 5310.517X₂; R² = 0.7244), where Y = coffee productivity (g plant⁻¹ year⁻¹), X₁ = CEC (mEq 100 g⁻¹), and X₂ = base saturation (mEq 100 g⁻¹). These findings suggest that the application of biopore infiltration holes has the potential to improve subsoil quality and enhance coffee productivity.